Study on variable temperature Mössbauer spectra of GdFe0.5Cr0.5O3 perovskite. (2nd September 2021) - Liu, Lebin; Mo, Jiajun; Chen, Haiwen; Liu, Min; Xia, Yanfang; Peng, Anguo
ABSTRACT: The synthesis of GdFe0.5 Cr0.5 O3 by sol-gel method was reported, and the cooling process of the sample was studied by Mössbauer spectroscopy. The Mössbauer spectra at room temperature reflect the characteristics of GdFe0.5 Cr0.5 O3 with orthogonally distorted perovskite structure, indicating that its Fe 3+ is a triangular or tetragonal distorted octahedron symmetric structure. With the decrease of temperature, the isomer shift and quadrupole splitting increase. The spectral transition from the doublet state at 250 K to the sextet state at 120 K reflects the magnetic phase transition in this temperature range. The observed magnetic field is a super-transferred hyperfine field (STHF) formed by the superexchange mechanism of oblique antiferromagnetic ordered Cr atoms.